Scientific basis for final competition preparation - Mujika, I. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
The taper phase before great competitions is most certainly the most significant step of the training season. Unfortunately, this period of time is usually the most questioned and doubted by trainers, and their method in this regard has merely remained purely empirical. In this article, we shall cover the scientific knowledge on taper planning, in order to help trainers facing this important moment of the season.